Pemanfaatan Media Digital dalam Menarik Minat Siswa di SD/MI Terhadap Pembelajaran PAI - Herlina, Herlina; Astuti, Mardiah; Triyunita, Haza; Rahmawati, Tri Diah; Yana, Nuzul (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the utilization of digital media in attracting the interest of elementary and Islamic elementary school (SD/MI) students in Islamic Religious Education (PAI) learning. The primary focus of this research is to identify effective types of digital media, their application methods, and the impact of their use on students' interest and understanding. The study employs a qualitative approach with a literature review method, using research data sourced from articles indexed in Google Scholar and Sinta. The findings reveal that various forms of digital media, such as audiovisual media, e-learning platforms (WhatsApp, Google Classroom, Zoom), storytelling, animations, YouTube, and the Shofun application, have been implemented in PAI learning. The utilization of these media can enhance students' motivation, creativity, and understanding of PAI materials. However, several obstacles are identified, such as teachers' limited understanding of technology and infrastructure constraints. The positive impacts of using digital media include facilitating material delivery, increasing student interaction, and overcoming spatial and temporal limitations. This study provides recommendations for educational practitioners to optimize the use of digital media to support more effective and engaging PAI learning for students